Optimizing charge transport in hybrid GaN-PEDOT:PSS/PMMADevice for advanced application - Makram A. Fakhri; Evan T. Salim; Marwah R. Ketab; Haneen D. Jabbar; Omar A. Ibrahim; Ahmad S. Azzahrani; Mohammed Jalal AbdulRazzaq; Raid A. Ismail; Ali Basem; Forat H. Alsultany; Subash C. B. Gopinath (Scientific Reports)
Abstract Organic–inorganic hybrid light-emitting devices have garnered significant attention in the last few years due to their potential. These devices integrate the superior electron mobility of inorganic semiconductors with the remarkable optoelectronic characteristics of organic semiconductors. The inquiry focused on analyzing the optical and electrical properties of a light-emitting heterojunction that combines p-type GaN with organic materials (PEDOT, PSS, and PMMA). This heterojunction is an organic–inorganic hybrid. The procedure entailed utilizing a spin-coating technique to apply a layer of either poly(methyl methacrylate) (PMMA) or a mixture of PMMA and poly(3,4ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT: PSS) onto an indium tin oxide (ITO) substrate. Subsequently, different Nd:YAG laser pulses (200, 250, and 300 pulses) were used to administer a GaN inorganic layer onto the prepared organic layer using a pulsed laser deposition approach. Subsequently, the thermal evaporation technique was employed to deposit an aluminum electrode on the top of the organic and inorganic layers, while laser pulses were fine-tuned for optimal performance. The Hall effect investigation verifies the p-type conductivity of the GaN material. The electroluminescence studies confirmed the production of blue light by the GaN-based devices throughout a range of voltage situations, spanning from 45 to 72 V.